Comparative Morphology and Phylogenetic Relatedness Among Bobwhites in Southern U.S. and Mexico - Shirley L. White; Kenneth R. Nolte; William P. Kuvlesky Jr.; Fred S. Guthery (National Quail Symposium Proceedings, 2017)
We analyzed the morphology and phylogenetic relatedness of masked bobwhites (Colinus virginianus ridgwayi) and Texas bobwhites (C. v. texanus) to determine if the numerically stable Texas bobwhite might serve as a reasonable research and management model for the endangered masked bobwhite. We compared 26 external and 24 internal morphological features. Texas and masked bobwhites had similar body mass; however, masked bobwhites had smaller head and body dimensions and longer wing and thigh bones (P < 0.01) than Texas bobwhites. Genomic DNA was extracted from heart or muscle tissue of captive masked bobwhites (n = 12) and from northern bobwhites obtained in Florida (n = 3), Tennessee (n = 5), Texas (n = 12), and Oklahoma (n = 3). Bobwhites from South Texas and masked bobwhites appear to form a relatively closely related assemblage, possibly representing a separate lineage from other bobwhite populations. Based on gross similarities between Texas and masked bobwhites in morphology and phylogenetic relatedness, as well as in habitat conditions on the semiarid rangelands they occupy, biological and management information from Texas bobwhites seems applicable to masked bobwhites.